A state space approach to the modelling and control of coupled, concurrent design tasks subjected to dynamically-changing disturbances - Ong, Kian Leong. (2008)
A linear state-space model of coupled, concurrent design iteration, called the Homogeneous State-Space (HSS) model, is proposed to analyse the stability and convergence rate of the design iterations.